The effectiveness of project tasks on students’ regional potential-based to increase students’ knowledge - Latifa, Dinda Khaira; Rezkilaturahmi, Rezkilaturahmi (Researcher and Lecturer Society, 2025)
The industrial world needs professionals who are able to align the needs of the market. Its intense market competition not only demands the ability to work, but also the ability to create innovative products. Therefore, higher education must prepare excellent graduates with those ability. One of the efforts is to improve the learning model by implementing Project Tasks on Students’ Regional Potential. This study belongs to pre-experimental research with a one-group pretest-posttest design, subjected to 30 students of D3 Mechanical Engineering study program. Based on the research results, it can be concluded that the students who were taught by Project Tasks on Students’ Regional Potential got significant improvement from their pre-test to post-test scores. Consequently, it can be interpreted as there was an effect of the Project Tasks treatment given to research subjects. Therefore, this model can be referred as an effective model to adapt, implemented on learning for vocational higher education.